The Increasing Public Knowledge Regarding PTSD (Post Traumatic Stress Disorder) In Gunung Lingai District, Samarinda City - Faizal Nur, Syukma Rhamadani; Samsugito, Iwan; Miharja, Ediyar; Anastasia Alenita Kara; Ananda Alivia Sityaningrum; Maura Gensa Rudit Santria; Mardika Nur Febrianti; Abdi Alfatih (Fakultas Kedokteran, Universitas Mulawarman, 2024)
Based on previous research, namely early detection of emotional disorders in the Gunung Lingai sub-district community, one of the characteristics of which is PTSD (Post Traumatic Stress Disorder) with the result that there are several people who experience this disorder. However, after exploring it more deeply, the results showed that the majority of people did not understand and know what PTSD was. This is also supported by statements from the public which state that they are less exposed to information about PTSD (Post Traumatic Stress Disorder) and this is also not something that is common or often discussed in society. To overcome this, the group provides health education related to PTSD (Post Traumatic Stress Disorder) to the people of RT.14 Gunung Lingai Village. Before and after providing health education, the group measured the level of community knowledge and obtained results in the form of an increase in their knowledge. Apart from that, several characteristics were also found that were related to the level of public knowledge regarding PTSD, including education, employment and gender.